Smallholders' cost efficiency in Mozambique: Implications for improved maize seed adoption - Helder Zavale; Edward Mabaya; Ralph Christy (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2005)
The objectives of this paper are to estimate cost efficiency and investigate factors influencing the cost efficiency of maize-growing smallholders in Mozambique. The data used in this study came from a national random sample of 4,908 smallholder farmers conducted by the Ministry of Agriculture and Rural Development in 2002. Stochastic cost frontier and self-selection bias methods are used. The results indicate that twelve out of twenty factors are significantly found to be the determining factors influencing the cost efficiency. To enhance the cost efficiency of producing maize, policy makers should put more emphasis on improving rural infrastructures, providing better education, and providing access to credit.
Keywords: 330; Kleinbäuerliche Landwirtschaft; Kosten-Wirksamkeits-Analyse; Maisanbau; Mosambik